THE EFFECT OF GOOD CORPORATE GOVERNANCE, LEVERAGE, AND COMPANY SIZE ON THE VALUE OF PROPERTY AND REAL ESTATE SECTOR COMPANIES - Putu Adella Sarianing; Komang Ayu Krisnadewi (Transpublika Publisher, 2024)
This study was meant to uncover the impact of good corporate governance, leverage, and company size on firms' value in the property and real estate sector listed on the Indonesia Stock Exchange for the period 2020-2022. The population taken into consideration in the research is the firm operating in the property and real estate sector listed on the IDX. The sample selection is by purposive sampling with certain criteria so that 81 data samples are obtained to be studied. The present investigation uses secondary data that came from financial records. The analysis of the data in this study was analyzed by utilizing SPSS for Windows software, which has given deep insight into the relationship between variables. According to the findings of the investigation, proper corporate governance represented by managers’ awareness is one of the factors that raise the worth of a business, in that increased stock ownership by management will lead to more motivation for performance improvement hence increasing the firm’s worth. If handled properly and effectively, leverage can enhance organizational value since increased leverage leads to increased company worth. On the other hand, when total assets are seen as being too large by investors who regard it as a bad signal therefore this may lead to decline in company value. Consequently, a negative relationship exist between company size and firm value.